Planilha eletrônica Excel e a matemática: Desenvolvimento de aplicativo para o ensino de matriz - Oliveira, Hélder Alves de (2011)
This paper aims to present the results of a qualitative research focused on the case study method, in which TICs have been used, following the assumptions of constructivist theory created by Seymuor Papert, in order to introduce the basic concepts of matrix algebra by using the Excel Spreadsheet software developed by Microsoft Corporation. To conduct the survey used the OA (Learning Objects) and a short course, and to introduce the concepts of addition, multiplication, and calculating the inverse of a given matrix, so that students could observe their applications in solving problems in context and launch hand this feature to solve systems of linear equations. Subsequently, we analyzed through a questionnaire, it showed that the majority of students, about seventy percent, considered attractive methodological proposal, demonstrating an interest in satisfying the content presented through technology. In this work, we infer a methodology for using Excel software in the teaching of matrix algebra.